Sodium hexachloroplatinate (IV) induces concentration- and time-dependent depolarization and cytotoxicity in HEI-OC1 auditory cells - Hamdy Embark; Kirsten Wissel; Gudrun Brandes; Andrej Kral; Thomas Lenarz; Nils Prenzler; Hannes Maier (PLoS ONE, 2026)
Over the past decades, cochlear implants (CIs) have been widely acknowledged for their efficacy and reliability in restoring auditory function in patients with severe to profound sensorineural hearing loss. Nonetheless, electrode corrosion involving platinum (Pt) components in CI systems can lead to increased electrode impedance and the release of Pt corrosion products, which possibly have toxic effects on cochlear sensorineural structures. Despite advances in CI technology, the biological responses, mediating cell damage, induced by platinum corrosion products following cochlear implantation remain incompletely characterized. To address this gap, we employed the H ouse E ar I nstitute– O rgan of C orti 1 (HEI-OC1) cell line as an in vitro auditory model to characterize the cytotoxic effects of sodium hexachloroplatinate (IV) (Na 2 [PtCl 6 ]) through electrophysiological analyses and relative quantification of mitochondrial oxidative activity. Using whole-cell patch-clamp recordings in current-clamp mode, we observed that Na 2 [PtCl 6 ] caused a significant, concentration- and time-dependent depolarization of resting membrane potentials, potentially facilitating activation of voltage-gated ion channels and disrupting ionic homeostasis. Consistent with the intracellular accumulation of Pt and the electrophysiological findings, significant concentration-dependent changes in oxidative activity were observed in HEI-OC1 cells following Na 2 [PtCl 6 ] exposure. No time-dependent differences in metabolic activity were detected after 24 h and 48 h of exposure, suggesting that cellular repair mechanisms may be activated in parallel during cultivation. Overall, these findings suggest that this Pt(IV) compound directly alters auditory cell electrophysiology, thereby promoting cytotoxicity. Understanding these mechanisms will improve the development of better implant materials, optimized stimulation pulse protocols, and protective therapies to enhance CI longevity and safety.